Application of “3X4”, “Communication”, Impulse – Poster Interactive Techniques in Teaching Medical Biology General Genetics (European Journal of Economics, Finance and Business Development, 2024)
This article describes the use of 3x4”, “communication” , impulse – poster interactive techniques in the teaching of medical biology general genetics and its theoretical foundations, conditions for the development of education and the process, essence, feature, development opportunities for the use of educational technologies.